2022
DOI: 10.1093/infdis/jiac216
|View full text |Cite
|
Sign up to set email alerts
|

Expected Impact of Universal Immunization With Nirsevimab Against RSV-Related Outcomes and Costs Among All US Infants in Their First RSV Season: A Static Model

Abstract: Background Respiratory syncytial virus (RSV) is associated with substantial morbidity in the United States, especially among infants. Nirsevimab, an investigational long-acting monoclonal antibody, was evaluated as an immunoprophylactic strategy for infants in their first RSV season and for its potential impact on RSV-associated, medically attended lower respiratory tract illness (RSV-MALRTI) and associated costs. Methods A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 35 publications
(52 reference statements)
3
24
0
1
Order By: Relevance
“…Kieffer et al [ 38 ] use a static decision analysis model to estimate that, without immunization, 1 in 7 infants have RSV MA-LRTI each year; that is, 47 281 hospitalizations (IP), 129 070 ED visits, and 353 563 OP visits, for a total of 529 915 encounters at an estimated cost of $124 billion annually. The authors go on to show that although IP visits accounted for 9% of encounters (24% ED visits; 67% OP visits), these encounters represented 91% of the annual RSV MA-LRTI economic burden, with mechanical ventilation (24%) and intensive care unit admissions (46%) composing 70% of those IP costs.…”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Kieffer et al [ 38 ] use a static decision analysis model to estimate that, without immunization, 1 in 7 infants have RSV MA-LRTI each year; that is, 47 281 hospitalizations (IP), 129 070 ED visits, and 353 563 OP visits, for a total of 529 915 encounters at an estimated cost of $124 billion annually. The authors go on to show that although IP visits accounted for 9% of encounters (24% ED visits; 67% OP visits), these encounters represented 91% of the annual RSV MA-LRTI economic burden, with mechanical ventilation (24%) and intensive care unit admissions (46%) composing 70% of those IP costs.…”
Section: Modelingmentioning
confidence: 99%
“…By contrast, palivizumab-eligible infants made up 6% of IP visits and 1% of ED and OP visits. Kieffer et al also show that 69% of all RSV MA-LRTI and 47% of IP RSV MA-LRTI occurred among infants born before the start of the season [ 38 ].…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate analysis using a static decision-analytic model that arrived at a considerably higher economic cost of RSV $1.2 billion showed that RSV hospitalization—despite contributing only 9% of the annual 529 915 healthcare case burden of RSV LRTI—resulted in 92% of the costs (27% hospitalization, 44% ICU admission, and 21% mechanical ventilation). In contrast, primary care and ED visits, although contributing to 91% of the healthcare burden, only accounted for 8% of the costs [ 34 ]. Because infant Medicaid recipients shoulder a major burden of RSV disease [ 19 ] and the associated costs [ 33 ], it is imperative that effective prevention measures also be offered to these infants [ 35 ].…”
mentioning
confidence: 99%
“…Indeed, the use of nirsevimab to prevent RSV infections and hospitalization shows its promising potential but studies on its cost-effectiveness are lacking. In a study by Kieffer and colleagues in 2022, it was estimated using a static model that universal immunization of all infants with nirsevimab is expected to reduce 290,174 RSV-MALRTI, 24,986 hospitalizations, and expenditures of $612 million USD ( 16 ). We therefore recommend that further studies be done to look into the applicability and cost-effectiveness of nirsevimab.…”
Section: Discussionmentioning
confidence: 99%